Moral values and methods of moral education at Samin community - Rinenggo, Alil; Kusdarini, Eny (Universitas Negeri Yogyakarta, 2021)
The research aims to describe the Samin community's moral values, the moral education methods applied by elder Samin, and the obstacles to moral education. The study uses a qualitative approach to ethnographic research. Data collection techniques are through in-depth interviews, participatory observation, and documentation. Data validated by source triangulation and technique triangulation. The research subjects were determined purposively, including Samin elders, the Samin community, and Klopoduwur Village Officials. The results showed that the Samin community had moral values of ancestral heritage categorized into three types: Panca Sesanti, Panca Wewaler, and Panca Peniten. The method applied is through oral traditions, wise words, habituation, role models, question and answer. Obstacles in moral education are negative stigma from other communities